2016
DOI: 10.5588/ijtld.16.0250
|View full text |Cite
|
Sign up to set email alerts
|

Active tuberculosis patients have high levels of IgA anti-alpha-crystallin and isocitrate lyase proteins

Abstract: ICL could be used in combination with other M. tuberculosis antigens to improve the sensitivity and specificity of current serological TB diagnostic methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…We encountered a similar phenomenon in this study, which resulted in 'negative' (< 0) ΔOD values for anti-Acr IgM antibodies. This observation was in complete contrast to some of the earlier studies which have shown high levels (OD >1.5) of anti-Acr IgM antibodies in ATB patients as well as healthy contacts [29,32,45,50]. Apart from the demographic differences in study populations, such discrepant results may also occur due to purely technical reasons.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…We encountered a similar phenomenon in this study, which resulted in 'negative' (< 0) ΔOD values for anti-Acr IgM antibodies. This observation was in complete contrast to some of the earlier studies which have shown high levels (OD >1.5) of anti-Acr IgM antibodies in ATB patients as well as healthy contacts [29,32,45,50]. Apart from the demographic differences in study populations, such discrepant results may also occur due to purely technical reasons.…”
Section: Discussioncontrasting
confidence: 98%
“…Further, like us, they had also observed a significant decline in their levels after successful treatment. Some other studies highlighting the diagnostic potential of anti-Acr IgA antibodies have been conducted by Abebe at al [29], Davidow et al [30], Legesse et al [41] and Talavera-Paulin et al [45]. Collectively, these studies emphasize the need to further explore the potential of anti-MtM IgM and anti-Acr IgA antibodies for the discrimination between HCWs and ATB.…”
Section: Discussionmentioning
confidence: 97%
“…High IgG antibody levels in TB patients have been reported in several studies and are believed to reflect the burden of infection [ 6 , 14 , 15 ]. High IgA levels against certain Mtb antigens have also been reported in patients [ 40 ]. The dominant IgM responses in LTBI have been reported previously by us as well as others.…”
Section: Discussionmentioning
confidence: 99%